In situ TEM investigations of the microstructural changes and radiation tolerance in SiC nanowhiskers irradiated with He ions at high temperatures. (15th May 2021) - Aradi, E.; Lewis-Fell, J.; Greaves, G.; Donnelly, S.E.; Hinks, J.A.
Abstract: Using in-situ transmission electron microscopy (TEM) with ion irradiation, we investigated the microstructural changes in silicon carbide nanowhiskers (SiC NWs) which were used as a model system for nanoporous SiC. Irradiations were carried out using 6 keV He ions at temperatures between 500 and 1000°C and doses up to 20 dpa. These results are compared with the irradiation effects in SiC thin foils under the same conditions to establish differences in their response to radiation damage. The irradiation temperature played a significant role in the evolution of different microstructures; at 500°C, small defect clusters were observed in the NWs together with a segregation of carbon at the surface of the NWs mapped using energy-filtered TEM (EFTEM). At 800°C, small He bubbles (2–4 nm in diameter) were observed in the NW matrix while He platelets and bubble discs formed in the foils. At 1000°C, several changes were observed in the NWs including bubbles at twin boundaries, voids and oxygen-rich precipitates. The large surface area to volume ratio enhances defect recombination supressing the defect density in the SiC NWs compared to the foils indicating high radiation tolerance; however, elemental segregation and precipitation may limit its application in advanced nuclear reactors. Graphical abstract: Image, graphical abstract